The Problem of Anomalous Filtration and Solute Transport in an Inhomogeneous Porous Medium (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The problem of anomalous transport and filtration of substance in a porous medium with a fractal structure is posed and numerically solved. The piezoconductivity equation proposed as fractional differential equations based on the anomalous Darcy law is proposed. The profiles of changes in the concentration of suspended particles, pressure and filtration velocity are determined. Various transport and filtration characteristics evaluated